Use of group work by experienced and Inexperienced lower secondary school english language teachers - Gelau, Anak Ragai. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This qualitative study was carried out to find the use of group work by experienced and inexperienced secondary school English language teachers and a case study method was employed. The respondents for the study are non-native English language teachers who are currently teaching in lower secondary school. 30 teachers were identified and they were classified into two categories: experienced teachers and inexperienced teachers. They were interviewed to collect the data. The data was analyzed using qualitative procedures and frequency counts and percentages were employed. The findings of the study indicated that there are differences in the use and organization of group work by the experienced teachers and inexperienced teachers. In view of that, a few recommendations were made